2014
DOI: 10.2478/pjct-2014-0058
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Polycomplexes of Poly(Methyl Vinyl Ether-Co-Maleic Anhydride) and Bovine Serum Albumin in the Presence of Copper Ions

Abstract: The binary and ternary complex formations of poly(methyl vinyl ether-co-maleic anhydride) (PMVEMA) with copper ions and with bovine serum albumin (BSA) in the presence of copper ions in phosphate buffer solution at pH = 7 were examined by the techniques of UV-visible, fl uorescence, dynamic light scattering, atomic force microscopy measurements. In the formation of binary complexes of PMVEMA-Cu(II), the addition of copper ions to the solution of PMVEMA in phosphate buffer solution at pH = 7 forms homogeneous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Copolymers of MVE with maleic anhydride are widely used in medicine and pharmacology, in paper and textile industries, for manufacture of cosmetics and toiletry, as bioadhesives for drug delivery options and components of cellulosic biocomposites . Besides, these copolymers form interpolymer complexes possessing valuable properties …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copolymers of MVE with maleic anhydride are widely used in medicine and pharmacology, in paper and textile industries, for manufacture of cosmetics and toiletry, as bioadhesives for drug delivery options and components of cellulosic biocomposites . Besides, these copolymers form interpolymer complexes possessing valuable properties …”
Section: Introductionmentioning
confidence: 99%
“…35,36 Besides, these copolymers form interpolymer complexes possessing valuable properties. 37 Industrially (BASF, GAF, Union Carbide), MVE is synthesized by vinylation of methanol with acetylene under elevated pressure (10-18 atm) at 120-160 ∘ C in the presence of alkali metal hydroxides or their alcoholates. [6][7][8] Furthermore, in acetylene chemistry a trend to replace free acetylene by CaC 2 , 17 particularly in the www.soci.org LN Parshina et al synthesis of vinyl ethers, [16][17][18][19][20][21][22] is gaining strength.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches are available to develop synthetic peptide-based vaccines, using metal ions in combination with peptide sequences. In particular, the investigation of the complex formation biopolymer by peptide in the presence of metal ions contributes greatly to the technological development of peptide-based vaccine prototypes [19]. The contact of the peptides with the polyelectrolyte (PE) is found at the interface.…”
Section: Peptide Vaccines Prototype and Immunitymentioning
confidence: 99%
“…The hydrophobic interactions in such a complex create an adjuvant effect for prototyping technology in vaccination. [19][20][21][22]. In the studies on the development of peptide vaccine prototypes previously made by our study group, it was observed that the purification of characterization of binding of synthetic peptides to various adjuvants and subsequent high immune response was obtained in BALB/c mice from experimental animals [23].…”
Section: Peptide Vaccines Prototype and Immunitymentioning
confidence: 99%
See 1 more Smart Citation